(untitled) (International Journal of Engineering and Computer Science, 2015)
Automatic license plate recognition is used to recognize the characters from license plate image. It is widely used in localized areas such as traffic control, burglary and surveillance. The proposed method applied on yellow color license plate. It has two main stages. First, exact location of the license plate is detected from an input image by using image acquisition and optical character recognition and sobel edge is used for character segmentation. Second, template matching is used to test the recognized characters with templates. This paper also proposed vehicle authorization by checking the license plate number from database and electronic mail is send to administrator if authorization fails.